2015
DOI: 10.1002/ejoc.201501053
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Diastereomeric β3‐Peptides from (R,R)/(S,S)‐APyC and (R)/(S)‐β3‐Caa: Determination of Enantiomeric Handedness

Abstract: We have previously reported enantiomeric α/β‐ and β‐peptides derived from aminopyrancarboxylic acids (APyCs). We now report the synthesis of diastereomeric β‐peptides synthesized from alternating (R,R)/(S,S)‐APyCs and C‐linked carbo β3‐amino acids [(R)/(S)‐β3‐Caas] and their conformational analysis. Extensive studies of these peptides revealed the presence of enantiomeric helical structures, that is, left‐ and right‐handed 12/10‐helices, that are well stabilized by five‐membered electrostatic interactions betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…For instance, in Europe and North America, acid precipitation imposed the soil acidification that caused forest decline. [96] Likewise in various regions of Australia, inappropriate N fertilizer, and continuous legume cultivation resulted in the soil acidification that resulted in abandoning of wheat cultivation due to Mn and Al toxicity. [95] Due to soil acidification caused either by the legume cultivation or other aforementioned processes, the activities of soil organisms are reduced, resulting in the inhibition of the decomposition of organic matter.…”
Section: Soil Phmentioning
confidence: 99%
“…For instance, in Europe and North America, acid precipitation imposed the soil acidification that caused forest decline. [96] Likewise in various regions of Australia, inappropriate N fertilizer, and continuous legume cultivation resulted in the soil acidification that resulted in abandoning of wheat cultivation due to Mn and Al toxicity. [95] Due to soil acidification caused either by the legume cultivation or other aforementioned processes, the activities of soil organisms are reduced, resulting in the inhibition of the decomposition of organic matter.…”
Section: Soil Phmentioning
confidence: 99%
“…These model drugs, differing in both their physico-chemical properties, were chosen mainly due to their different binding sites on the HSA molecule, resulting also in different binding strength. Whereas the earlier ED and CD studies of Chamouard et al reported two binding sites for DCF with HSA: the highaffinity binding site Sudlow II and the low-affinity binding site Sudlow I [14], the recent finding by Sharma et al by ITC was a good fit a single-binding Sudlow II site model with a moderate K b [15]. In contrast, the crystallographic study discovered and the ED and ITC confirmed LIDO binding to a unique low-affinity site formed of residues from subdomain IB [16].…”
Section: Resultsmentioning
confidence: 99%
“…Pyrrolidine derivatives are also valuable chiral building blocks for the synthesis of more complex compounds and therefore can be useful as chiral auxiliaries and ligands for asymmetric synthesis . The moiety has also attracted much attention as a result of varied pharmacological properties displayed by its derivatives which include antagonists, cholinesterase inhibitory, antimicrobial, antitumor, anti‐inflammatory, anti‐HIV, antidiabetic, Mcl‐1 inhibitors and anticancer properties . Chalcones were first isolated from flavonoid biosynthesis in plants and since then many studies have been focused on structural modifications of the chalcone scaffold and the large variety of its biological activities .…”
Section: Introductionmentioning
confidence: 99%